Deter1nination of Adenosin De Aminase (ADA) enzyme activity in patients with Salmonellosis - Khalil, H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
!’hi_, i1rycsligation was carried ou1 dn J)Ct’iphcral blom.l s_amplc:s. wl1ich wendrawiÂ·1 ih)rl1 patients w.ith l)1).hoid !’ever. Fifteen palic111 nging ]5- 45 years old .<iS vvdl as ten sample::. w:cr: cÂ·ollec ted from healthy persons-al the same range of age. Sera were used t’or csti niation the act i vity and sp ci fie activity of t.A. The resuJts sho:Â«"’d sig11ltl’c u1t increase i11 the cruymc nctivity and specitk acti;vity ortbc patlcn1s in compatisbn vdtb controL